Low-dimensional Magnetism and Antiferromagnetic Ordering in the Mixed-valence Spin-chain Cuprate TlCu2O2 - Frei, Maren; Schnelle, Walter; Felser, Claudia; Jansen, Martin (Zeitschrift für Anorganische und Allgemeine Chemie, 2020)
TlCu2O2, a mixed-valence spin-chain cuprate, was synthesized in a piston cylinder system starting from thallium sesquioxide Tl2O3, cuprous oxide Cu2O and copper powder. The main structural characteristics are edge-sharing (CuO2)n zigzag chains, which are linked in the perpendicular crystallographic direction by Cu+ to form a three-dimensional network. Data from magnetic susceptibility and specific heat measurements show features typical for low-dimensional magnetic exchange interactions. The long-range antiferromagnetic ordering is observed at TN = 19.7 K. No weak ferromagnetic component can be detected, suggesting a plain Néel-type spin-ordered structure.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Copper; Copper; Copper oxide chains; Copper oxide chains; Copper oxide chains; Low-dimensional magnetism; Mixed-valence compound; Mixed-valence compound; Mixed-valence compound; Mixed-valence compound; Mixed-valence compound; Spin-chain cuprate; Spin-chain cuprate; Spin-chain cuprate; Spin-chain cuprate